2013
DOI: 10.1523/jneurosci.3042-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Appetitive Learning Requires the Alpha1-Like Octopamine Receptor OAMB in theDrosophilaMushroom Body Neurons

Abstract: Associative learning is a fundamental form of behavioral plasticity. Octopamine plays central roles in various learning types in invertebrates, however the target receptors and underlying mechanisms are poorly understood. Drosophila provides a powerful system to uncover the mechanisms for learning and memory. Here, we report that OAMB in the mushroom body neurons mediates the octopamine’s signal for appetitive olfactory learning. The octopamine receptor OAMB has two isoforms (OAMB-K3 and OAMB-AS), differing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 27 publications
(47 reference statements)
11
76
0
Order By: Relevance
“…2; Schwaerzel et al 2003;Kim et al 2007). Similarly, optoor thermogenetic stimulation of octopaminergic neurons (OAn) is sufficient for appetitive learning (Schroll et al 2006;Burke et al 2012), and mutants for the expression of the octopamine receptor, OAMB, in the a/b and g MBn are impaired in reward learning (Kim et al 2013). These observations are all consistent with the original idea that the rewarding US is conveyed through the octopaminergic system and OAMB (Fig.…”
Section: Dopamine Neuronssupporting
confidence: 73%
See 1 more Smart Citation
“…2; Schwaerzel et al 2003;Kim et al 2007). Similarly, optoor thermogenetic stimulation of octopaminergic neurons (OAn) is sufficient for appetitive learning (Schroll et al 2006;Burke et al 2012), and mutants for the expression of the octopamine receptor, OAMB, in the a/b and g MBn are impaired in reward learning (Kim et al 2013). These observations are all consistent with the original idea that the rewarding US is conveyed through the octopaminergic system and OAMB (Fig.…”
Section: Dopamine Neuronssupporting
confidence: 73%
“…1, 2). The subsequent isolation of dopamine (DA) and octopamine (OA) receptor genes and mutants (Han et al 1996Kim et al 2003Kim et al , 2007Kim et al , 2013 along with other reagents allowed this specific hypothesis to be tested (Schwaerzel et al 2003), which produced results consistent with the broad model that the US pathway for aversive conditioning is mediated by G-protein-coupled DA receptors expressed by the MBn and that the US pathway for appetitive conditioning is mediated by both G-protein coupled OA and DA receptors expressed by the MBn (Connolly et al 1996;Schwaerzel et al 2003;Kim et al 2007Kim et al , 2013. The CS and US coincidence integration in the MBn occurs, at least in part, through the activity of an adenylyl cyclase encoded by the rutabaga (rut) gene (Tomchik and Davis 2009).…”
Section: Neural Circuit Model For Olfactory Memory Formationmentioning
confidence: 99%
“…Dysregulated genes required at synapses and in cell-cell communication included genes that encode immunoglobulin domain transmembrane proteins involved in determining the specificity of synaptic connections between neurons and their target cells (Carrillo et al, 2015). Within the G-protein signaling category, notable genes included those required for the production ( Tdc1 , Tdc2 ) and reception ( Oamb , Octbeta3R ) of the neurotransmitter octopamine that is well-established to be necessary for appetitive olfactory short-term learning and memory (Kim et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Most important with regard to this aspect is the Oamb receptor that was named according to its high expression levels in the mushroom bodies (OA receptor primarily expressed in mushroom bodies; Han et al 1998). Recently, it has been shown that Oamb is required for appetitive learning in the fly (Kim et al 2013). A very elegant study revealed the involvement of the Oamb receptor as well as of Octß2R in different aspects of olfactory learning in the fly, indicative of a complex role of octopaminergic signaling in this process (Burke et al 2012).…”
Section: Discussionmentioning
confidence: 99%